Effects of obesity on the cardiac proteome - Fernandes Vileigas, Danielle [UNESP]; Cicogna, Antonio Carlos [UNESP] (Elsevier, 2021)
Obesity has reached epidemic proportions in both developed and developing countries. It is currently recognized as a major health concern due to excessive adipose tissue which is associated with a wide range of other medical complications, such as cardiovascular disease. Obesity causes severe changes in the heart and can induce modifications in cardiac structure and function, predisposing the development of heart failure. However, the mechanisms behind functional heart damage when faced with excess adipose tissue are not completely understood. Mass spectrometry-based proteomics is a powerful tool for studying the biology of systems at the protein level. It can provide a systematic, global, unbiased, and quantitative assessment of proteins, clarifying molecular based involvement in disease pathophysiology. Such knowledge is essential for shedding light on diagnosis and the development of therapeutic strategies. Thus, this review summarizes the basis of cardiac remodeling in obesity and current proteomics methods, as well as focusing on the contribution of proteomics in better understanding the molecular mechanisms underlying heart diseases in obesity research.
Keywords: Biological systems; Cardiac remodeling; Cardiometabolic disease; Cardiovascular diseases; Mass spectrometry; Obesity; Proteomics